Impact of FTA on Philippine industries: Analysis of network effects - Francis Mark A. Quimba; Mark Anthony A. Barral; Maureen Ane D. Rosellon; Sylwyn C. Calizo (Philippine Institute for Development Studies (PIDS), 2020)
Trade is an important component of the Philippine economy. Contemporary trade is shaped primarily by the evolution of Global Value Chains (GVCs), and this has a significant implication in integrating developing countries, such as the Philippines, into the global economy. An economy's inclusion into GVCs is affected by different factors, one of which is through a Free Trade Agreement (FTA). The impact of FTAs has long been studied in the Philippines, but the network effects of FTA trade shocks and its resulting impact to industry firm performance have not been explored as much. This study contributes to filling that gap by calculating the direct impact of trade agreements to the performance of various sectors. The results of the analysis show that FTA imports have a positive and significant direct effect on industry growth and labor productivity. The network effects, however, are not statistically significant for real Gross Value Added growth. On employment, the direct effect is negative and statistically significant, but the network effects would temper this effect because the upstream effect arising from customers is positive and statistically significant. The shock also has a positive and statistically significant direct effect on labor productivity, which implies that increasing imports increases labor productivity of Philippine sectors.
Keywords: 330; Trade; network effects; trade agreements; FTA; Philippines